PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA DINAS SOSIAL KABUPATEN BIREUEN - Yanto, Ferri; Yanti, Ira Dama; Fazira, Nanda (Fakultas Ekonomi, 2024)
This study discusses the influence of motivation and workplace conditions on the job satisfaction of employees of the Bireuen Regency Social Service. The aim is to find out how the work environment and employee motivation impact their job satisfaction individually and simultaneously. Before hypothesis testing and data analysis, the sample of this study consisted of 47 employees of the Bireuen Regency Social Service. Of the 47 people who responded, 24 were civil servants and 23 were honorary employees of the Bireuen Regency Social Service. Multiple linear regression analysis was used to evaluate how the variables discussed in the study interact with each other. Partially, the job satisfaction of employees of the Bireuen Regency Social Service is positively and significantly influenced by their work motivation. In addition, the work environment of employees of the Bireuen Regency Social Service partially has a positive and significant effect on their satisfaction with their work. In addition, the work environment also has a substantial effect on their motivation to work, which has a unidirectional and significant impact on their satisfaction with their work. Motivation and work environment affect employee job satisfaction by 46.1%. Other variables not included in this research model have an effect of 53.9%. Keywords: Work Motivation, Work Environment, Job Satisfaction